405 Impacts of 40. (7th December 2018) - Whittier, J; Bruns, K; Funston, R; Volesky, J; Klopfenstein, T; Adams, D
Abstract: Our objective is to describe impact on beef and range management systems resulting from visionary development of a working research ranch in the Nebraska Sandhills by the University of Nebraska (UNL). Gudmundsen Sandhills Laboratory (GSL) is a 12, 800-acre research ranch in the Nebraska Sandhills. In 1978, Elmer "Pete" and Abbie Gudmundsen gifted the former Rafter C Ranch to the University of Nebraska Foundation. To the credit of UNL Administration, GSL development for range livestock research was delegated to a team chaired by Dr. Don Clanton. This team configured the ranch to investigate production and management questions pertinent to the region. Major evolution of impacts on beef and range systems from GSL are: 1) Protein, rather than high levels of starch, is the preferred winter supplement for Sandhills forages; 2) Production systems using self-harvesting by grazing are typically most economical in Sandhills cow-calf systems; 3) Development and implementation of a systems approach to research while training students in systems thinking; 4) June versus March calving for the Nebraska Sandhills beef systems best matches rangeland quality and quantity; 5) Validation of the NRC model in Sandhills systems; 6) Distillers grains provide a beneficial nutrient profile for gestating cows and yearlings when grazing cool-season meadow and upland range and will extend range capacity; 7) Time and type of supplementation affect prenatal fetal programming to impact changes in BCS, weight, carcass traits and cow productivity through epigenetic mechanisms; 8) Nebraska Ranch Practicum at GSL provides valuable, science-based, systems education to clientele in multiple states; 9) Heifer development systems are a key component of sustainable beef systems in the Nebraska Sandhills. 10) Proper sub-irrigated meadow management offers a key component to profitable forage management systems. We conclude that GSL provides an important resource for solving ranching problems in beef systems.